The Role of KKN Students in the Era of Digitalization of Education in Gabanganom Wetan Village - Muhammad Syifa’ Nuqoba; Tasya Kurnia Yulia Putri; Alfiani Anditasari; Muhammad Zaki Adnan; Nova Riyanti; Eni Faujiyah Mailani; Syarifatul Aulia; Aghina Ragil Sugesta; Sulistio Sulistio (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
In digitalization, education is a crucial element in developing individual potential and intelligence. To carry out education effectively in the era of digitalization, teaching staff are needed who can teach in formal and non-formal contexts, of course with their competencies. Our Real Work Lectures (KKN) are held in Gebanganom Wetan Village, Kangkung District, with the main aim of providing community service and supporting the improvement of children's education in the village. Even though the enthusiasm and passion for learning among children in Gebanganom Wetan Village is very high, the shortage of teaching staff is a major obstacle to achieving maximum education. This article is entitled "The Role of KKN Students in the Era of Digitalization of Education in Gebanganom Wetan Village." This research uses the Participatory Action Research (PAR) method and carries out field observations to identify potential and problems in the village. The results of KKN activities provide an illustration of the enthusiasm and enthusiasm of children and the community for education in the era of digitalization from the role of students as teaching staff in supporting education in Gebanganom Wetan Village through various formal and non-formal education activities carried out by KKN Group 124